The impact of green building ratings programs on business decisions - Quiroga, Lisa Marie, author; Strong, Kelly, advisor; Glick, Scott, committee member; Tremblay, Kenneth, committee member (Colorado State University. Libraries, 2014)
The purpose of this research is to expand knowledge about the usefulness of green building rating programs for businesses which already participate in green building, and also for those considering participating in green building. This knowledge is important to both businesses interested in green building, and also for universities teaching classes with green building practices in mind. The research revealed that, while there is growing environmental concern among specialists in the energy design and construction industry, green building alternatives are generally cost prohibitive, and the life cycle cost benefits are insufficient to warrant the use of new material or systems without the support of government subsidies.
Keywords: alternative energy; business decisions; green building ratings programs; leadership in energy and efficient design; LEED; qualtrics